Games of conflict and cooperation in Asia - Suzuki , Motoshi ; Okada , Akira (Springer, 2020)
Contents: A relational approach to the study of international relations in Asia Signaling game of collective self-defense in the U. S. - Japan alliance Information sharing in early stage international disputes : how China and Japan communicate Peacekeeping by the UN and regional organizations : sharing the burden or passing the buck? Politics over the claim of individual self-defense at wars : aid conditionality and reciprocity in Asian regional conflict International cooperation and institution formation : a game of theoretic perspective An agenda-setting game of the Landmine Ban Treaty FTA EPA negotiations and domestic reforms in two-level games analysis The paradox of compliance : does legalization increase compliance in trade disputes? Analyzing international development loan markets with rival lenders Globalism and regionalism : the East Asian currency crisis and institutional building